PENGARUH MODEL COOPERATIVE SCRIPT TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI KELAS V SDN JOGLO 09 JAKARTA BARAT - Jannah, Azzahra Wardatul; Latifah, Nur; Magdalena, Ina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Thesis of the Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Tangerang 2023. This study aims to determine the effect of the cooperative script model on the descriptive essay writing skills of fifth grade students at SDN Joglo 09 West Jakarta. This research is a type of experimental research in the form of a quasi-experimental. The variables of this study consisted of the independent variables of the cooperative script model and the dependent variable, namely descriptive essay writing skills. The population in this study was the fifth grade students at SDN Joglo 09 West Jakarta, totaling 64 students consisting of 32 VA class students as the control class and 32 VB class students as the experimental class. Learning the skills of writing descriptive essays using the cooperative script model is better than the conventional learning model